UMPSA and Malaysian Education Strengthen Relations with Institutions in China - Mohd Ferdaus, Musa (UMPSA, 2023)
HEBEI, 19 September 2023 - The Malaysian Education delegation to China, attended by the Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato' Ts. Dr. Yuserrie Zainuddin, and the Deputy Director-General of Research and International Affairs at the Department of Higher Education, Ahmad Rizal Adnan, paid a courtesy visit to Hebei University (HBU).